Investigation of the expression level of genes-markers of proliferative activity in the mucosa at normal and various pathologies of the colon - T. M. Kulinich; M. V. Zakharenko; E. L. Dzhikiya; A. L. Senchukova; U. S. Stanoevich; I. B. Grunin; N. V. Melnikova; S. V. Goncharov; T. V. Krashikhina; E. A. Kudinova; O. P. Bliznyukov; V. K. Bozhenko (Успехи молекулярной онкологии, 2020)
Background. The search for molecular markers of colon diseases allowing highly specific and sensitive identification and differentiation of pathological processes is a clinically important problem. Expression levels of genes responsible for proliferation can reflect the changes in the affected tissues. The study objective is to perform comparative analysis of molecular and genetic markers of proliferative activity in benign and malignant neoplasms of the colon. Materials and methods. Analysis of the changes in proliferation markers (CCND1, с-MYC, Ki-67, HER2neu, TERT) in adenocarcinoma of the colon (n = 259), resection margin (about 15–20 cm from the tumor lesion) (n = 251), unchanged colon mucosa from healthy donors (n = 247), polyps (n = 28), unchanged colon mucosa intestinal polyposis (10–15 cm from the polyp) (n = 75) was performed using RT-PCR. Results and conclusion. It was shown that morphologically unchanged tissue of intestinal mucosa in malignant tumors has significant differences from normal tissue of healthy donors. Significant differences in the level of expression of genes responsible for the processes of proliferation, с-MYC, CCND1, TERT were found in benign hyperproliferative diseases (polyps). Moreover, these changes were specific to the type of pathological process, which allows us to consider these genes as the most promising candidates in the development of a differential method for diagnosing colon diseases.